Baobando em uma formação de raiz africana com professoras(es) e núcleo gestor da educação básica na cidade de Crato-CE - Silva, Samuel Morais (2018)
The present study is based on an ongoing experiment in the project entitled Memórias de Baobá, which is being carried out at the School of Early Childhood Education and Primary Education I March 08. Institution linked to the municipal education network of the city of Crato, in the region of Cariri, south of Ceará. The project aims, since May 2014, to implement Law No. 10,639 / 03, which reformulated LDB (9,394 / 96) with the advent of the National Curricular Guidelines for Education of Ethnic and Racial Relations and for the Teaching of African and Afro History and Culture which determines public and private school establishments at the national level, the obligation of contents and methodologies that will jeopardize the studies of Africa and its inheritances. However, it was observed that the educational actions carried out in the project between the years 2014 and 2016, with a view to implementing the aforementioned law, did not account for its implementation in the curricular matrix of the school. This statement is justified after the teachers report difficulties in articulating such contents in their educational practices. In this sense, the need for a continuous formation with the teachers and school management was observed, starting from the principles / teachings of the African Worldview, trying to construct a pedagogical proposal that valorized the African repertories marked in the local culture. In order to do so, we carried out an African Root Research-Formation anchored in Baobá Pedagogy and based on the contribution of Pretagogy, attempting to construct said proposal and, through this, to discover pedagogical practices that give subsidies to teachers and management nucleus, in the treatment African and Afro-Brazilian history and culture, as well as to verify that contributions to the training that values the principles / teachings of the African Worldview, could bring to the curricular matrix of the school, around the local african education and education for ethnic- racial relations. Thus, we proposed to work with methodological references and pedagogical approaches equipped with knowledge and knowledge of the African matrix. In this sense, the methodological paths are constituted by authors and authors, such as Josso (2004), Petit (2015), Petit e Silva (2011) and Oliveira (2007). In addition to Cavalleiro (2001), Silva (2010), Oliveira (2006), Meijer (2012), Books (2017) and Macedo (2012), help us reflect on African root formation, school africanization and decolonization of the curriculum, from the conceptual foundational categories that enriches the theoretical basis of the research, concepts such as: Anti-Racist Education, African Worldview, Africanities, Curriculum and Teaching.